2013
DOI: 10.1158/1535-7163.mct-13-0012
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 Hypermethylation Is a Potential Biomarker of Sensitivity to Antimitotic Chemotherapy in Endocrine-Resistant Breast Cancer

Abstract: Overexpression of the antiapoptotic factor BCL-2 is a frequent feature of malignant disease and is commonly associated with poor prognosis and resistance to conventional chemotherapy. In breast cancer, however, high BCL-2 expression is associated with favorable prognosis, estrogen receptor (ER) positivity, and low tumor grade, whereas low expression is included in several molecular signatures associated with resistance to endocrine therapy. In the present study, we correlate BCL-2 expression and DNA methylatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 49 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…A clinical study is now underway in Australia to explore the venetoclax-tamoxifen combination in patients with metastatic ER-positive HER2-non-amplified breast cancer (see Table 1). Treatment with ABT-737 has also been shown to restore sensitivity to paclitaxel in endocrine-resistant breast cancer (129). Additional approaches combining BH3 mimetics with investigational agents such as PI3K/mTOR inhibitors (130, 131) and gamma secretase inhibitors (132) are also being explored to bypass resistance mechanisms and enhance efficacy.…”
Section: Future Considerations and Conclusionmentioning
confidence: 99%
“…A clinical study is now underway in Australia to explore the venetoclax-tamoxifen combination in patients with metastatic ER-positive HER2-non-amplified breast cancer (see Table 1). Treatment with ABT-737 has also been shown to restore sensitivity to paclitaxel in endocrine-resistant breast cancer (129). Additional approaches combining BH3 mimetics with investigational agents such as PI3K/mTOR inhibitors (130, 131) and gamma secretase inhibitors (132) are also being explored to bypass resistance mechanisms and enhance efficacy.…”
Section: Future Considerations and Conclusionmentioning
confidence: 99%
“…The serine/threonine kinase PLK1 governs several mitotic stages, including entry into mitosis, centrosome maturation, bipolar spindle assembly, activation of the anaphase-promoting complex/cyclosome by phosphorylation of early mitotic inhibitor 1, chromosome segregation and mitotic exit (4). The overexpression of PLK1 is associated with a poor prognosis in a variety of cancers (5)(6)(7)(8)(9). Beyond the regulation of mitosis, PLK1 possesses cancer cell-specific functions in G1/S transition and DNA replication (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have documented aberrant methylation events in breast carcinogenesis and identified specific DNA methylation biomarkers that have significant diagnostic and prognostic potential [9][10][11][12] . Several studies have also identified DNA methylation signatures that can distinguish between breast cancer subtypes [13][14][15][16] , and others that may be predictive of treatment response [17][18][19] .…”
mentioning
confidence: 99%